Morphological forms and viability of Campylobacter species studied by electron microscopy. - NG, L K (1985)
Electron microscopic studies of Campylobacter revealed that different morphological forms predominate at different parts of a colony. At the periphery, cells were almost all spirals, while in the center of the colony cells were mainly coccus shaped. Unusual ring-shaped cells, "donuts", were observed in the raised, peripheral region of the colony. Donut or ring forms have not previously been reported for Campylobacter organisms. Our data indicate that young or actively growing cells are mainly spiral shaped. Older cells undergo a degenerative change to coccoid forms. The donut shape appears to be an intermediate stage between spirals and cocci. Comparisons of plate counts of actively growing and inactive cells confirmed that coccoid cells are probably nonviable.